10 Accountancy - Overlap between Communication and Harmonization - Alexandru TRIFU; Loredana TEREC -VLAD (Association of Social and Educational Innovation, 2014)
The relationship between accountancy and communication is easily understandable especially from the investors' point of view. Since until recently almost every country had its own accounting language, the introduction of the international financial reporting standards led to an increase in competitiveness and competition especially in the international market. Specialists believe that this is mainly due to accountancy, but we cannot deny that accounting communication as a process of transmitting the information was also a determining factor. The aim of this article is to highlight the importance of the accounting communication process and especially the importance of the international financial reporting standards, since we live in a society where competitiveness makes the difference between success and failure and information is power. It is also important to emphasize that accounting education plays a key role especially when it comes to investments.